The Other in His Impotence: The Problem of Multiplicity across Deleuze, Laplanche, and Lacan - Holmberg, Rafael (Cosmos and History: The Journal of Natural and Social Philosophy, 2024)
A similar framing of inarticulable formations, of pure multiplicities, marks the respective projects of Deleuze and Laplanche. The absolute exteriority of a disjunctive multiplicity is re-inscribed as a relativised, interiorised trace. This trace-logic of Deleuze and Laplanche has definitive implications where the psychoanalytic subject and the unconscious is concerned. However, there is a difficulty in this logic of accounting for the unconscious formations enumerated by Freud (slips of the tongue, jokes, symptoms etc.). In turning to Lacan, however, the positions of Deleuze and Laplanche can be illuminated (despite their attempt to ‘move beyond’ him). We see the trace in its material, unconscious substantiality upheld by the function of the big Other as an absent centre to which discourse is referred and through which the speaking subject is revealed as being in a discrepant relation to itself. The big Other, in his function as intimate, yet lacking, alterity, seems to help to resolve the problematic of multiplicity for Deleuze and Laplanche.